DAMPAK COVID- 19 PADA KESEHATAN MENTAL TENAGA KESEHATAN DI RUMAH SAKIT RUJUKAN COVID-19 RUMAH SAKIT UNIVERSITAS UDAYANA TAHUN 2021 - Iswari, Anak Agung Putu Tia Pradyana; Putri, Wayan Citra Wulan Sucipta (ARCHIVE OF COMMUNITY HEALTH, 2023)
ABSTRACT Health workers as the frontline facing the covid-19 outbreak professionally treat patients so that they have concerns about the health of individuals and their families that have the potential to cause mental health problems such as fear, anxiety, stigma, marginalization of people with diseases and stress due to job demands. This study aims to determine the impact of COVID-19 on the mental health of health workers at UNUD hospital in 2021. This research is cross sectional research using Google Form link questionnaire. The sample is health workers who work and registered in UNUD hospital using convenience sampling technique with data collected as many as 110 people. The results showed that 92.73% of health workers did not experience depression, 7.27% mild depression, 65.45% did not experience anxiety, 34.55% mild anxiety, 76.36% did not experience stress and 23.64% mild stress. Factors of profession, having family members with chronic diseases, availability of information on the use of PPE, family support, incentives related to the impact of mental health (p<0.05). Factors not related to the impact of mental health are gender, education, marital status, living with children, living with the elderly, installation, length of Service, Compensation, hours and rest facilities (p>0.05). It is necessary to pay special attention by holding free counseling in order to still create conducive and healthy working conditions. Keyword : Health Workers, Mental Health, Depression, Anxiety, Stress   ABSTRAK Tenaga kesehatan sebagai garda terdepan menghadapi wabah COVID-19 secara profesional merawat pasien sehingga mempunyai kekhawatiran mengenai kesehatan individu dan keluarganya yang berpotensi menimbulkan masalah kesehatan mental seperti ketakutan, kecemasan, stigma, marginalisasi terhadap penderita penyakit dan stress akibat tuntutan pekerjaan. Penelitian ini bertujuan untuk mengetahui dampak COVID-19 pada kesehatan mental tenaga kesehatan di RS Unud tahun 2021. Penelitian ini adalah penelitian cross sectional menggunakan kuesioner link google form. Sampel adalah tenaga kesehatan yang bekerja dan terdaftar di RS Unud menggunakan teknik convenience sampling dengan data terkumpul sebanyak 110 orang . Hasil penelitian menunjukkan 92,73% tenaga kesehatan tidak mengalami depresi, 7,27% depresi ringan, 65,45% tidak mengalami kecemasan, 34,55% kecemasan ringan, 76,36% tidak mengalami stress dan 23,64% stress ringan. Faktor profesi, memiliki anggota keluarga dengan penyakit kronis, ketersediaan informasi tentang penggunaan APD, dukungan keluarga, insentif berhubungan dengan dampak kesehatan mental (p<0,05). Faktor-faktor yang tidak berhubungan dengan dampak kesehatan mental yaitu jenis kelamin, pendidikan, status pernikahan, tinggal dengan anak, tinggal dengan lansia, instalasi, masa kerja, kompensasi, jam dan fasilitas istirahat (p>0,05). Perlu memberikan perhatian khusus dengan mengadakan konseling gratis supaya tetap menciptakan kondisi kerja yang kondusif dan sehat. Kata Kunci : Tenaga Kesehatan, Kesehatan Mental, Depresi, Kecemasan, Stres